Analisis Peran Model Praktikum Problem Solving Laboratory dan Higher Order Thinking Labotarory dalam Meningkatkan Keterampilan Abad 21 - Hasanah, Ayuning Nur; Malik, Adam (Edusainstika: Jurnal Pembelajaran MIPA, 2025)
This study was conducted with the aim of analyzing the role of the Problem Solving Laboratory (PSL) and Higher Other Laboratory (HOTLab) activity models in improving 21st century skills. The method used is literature review or library research, which is a series of studies related to literature collection methods or research whose research object is a variety of library information, namely a review of studies that have been conducted previously regarding the role of the Problem Solving Laboratory and Higher Other Thinking Laboratory practicum models in improving 21st century skills. 21st century skills refer to a set of abilities that are considered important for one's success in the current era of information and globalization. The analysis of the role of Problem Solving Laboratory (PSL) and Higher Other Thinking Laboratory (HOTLab) activity models in 21st century learning provides important insights into how these two models contribute to developing the skills necessary for success in the modern era, namely: development of critical skills, facilitation of collaborative learning, enhancement of problem solving skills, relevance to current and future challenges and facilitation of independent learning. The Problem Solving Laboratory (PSL) is specifically designed to assist students in developing problem solving skills and the Higher Order Thinking Laboratory (HOTLab) is designed to enhance critical thinking skills. PSL and HOTLab are not only conventional learning facilities, but also platforms that enable students to develop 21st century skills essential for success in today's information age and globalization.